Enhanced ethanol selectivity of flame-spray-made Au/ZnO Thick Films - V. Kruefu (2018)
Copyright © 2014 American Scientific Publishers All rights reserved. Sensing characteristics of the spin-coated Au/ZnO nanoparticles thick films with different Au concentrations have been studied for various gases, namely, CO, SO2, ethanol and acetone. The influence on a dynamic range of Au concentration on ethanol response (0.005-0.1 vol.%) of thick film sensor elements was studied at the operating temperatures ranging from 300 to 400 °C in the presence of dry air. The optimum Au concentration was found to be 0.5 mol%. 0.5 mol% Au exhibited an optimum ethanol response of 5.0 × 102and a short response time (10 s) for ethanol concentration of 0.1 vol.% at 400 °C. Plausible mechanisms explaining the enhanced ethanol selectivity by thick films of Au/ZnO are discussed.